The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11606-013-2466-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Literacy on Desire for Participation in Healthcare, Medical Visit Communication, and Patient Reported Outcomes among Patients with Hypertension

Abstract: Patients with low and adequate literacy were similarly interested in participating in medical decision making. However, low literacy patients were less likely to experience PDM in their visits. Low literacy patients in the intensive physician intervention groups asked fewer medical questions. Patients with low literacy may be less able to respond to physicians' use of patient-centered communication approaches than adequate literacy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 33 publications
6
148
2
1
Order By: Relevance
“…However, no difference was found between two groups in visiting the doctor. Hence, the effect of health literacy should be considered in use of educational tools to improve understanding blood pressure knowledge in future studies [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no difference was found between two groups in visiting the doctor. Hence, the effect of health literacy should be considered in use of educational tools to improve understanding blood pressure knowledge in future studies [2].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained by Pandit et al showed health literacy as an important predictor of blood pressure control [11]. Aboumatar et al study also points out the effect of higher health literacy on improvement in hypertension [2].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, it has been documented that patients with lower literacy levels tend to ask fewer questions and make fewer requests for information, and our HCPs' comments support these reports. 38,39 Often, low SES patients are minority patients. 40 In the United States, the quality of health care for minority patients compared to Whites has been extensively documented, underscoring that minority patients receive lower quality interpersonal care.…”
Section: Discussionmentioning
confidence: 99%
“…One major concern with low literacy can be linked to reduced selfcare behaviors in cardiac patients. In addition, low health literacy has been associated with lower BP control and reduced participation in medical decisions, 101,111 reduced communication with providers, 120 lower disease knowledge, 103,104,115 reduced cognition, 112 lower medication adherence levels, 123 and lower medication refill adherence.…”
Section: Question 3 How Are Common Barriers To Implementing Tpe Formentioning
confidence: 99%